2023
DOI: 10.1186/s12864-023-09450-x
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and characterization of Glutathione S-Transferases (GSTs) and their expression profile under abiotic stresses in tobacco (Nicotiana tabacum L.)

Abstract: Background Glutathione S-transferases (GSTs) are large and multifunctional proteases that play an important role in detoxification, protection against biotic and abiotic stresses, and secondary metabolite transportation which is essential for plant growth and development. However, there is limited research on the identification and function of NtGSTs. Results This study uses K326 and other six tobacco varieties (Hongda, HG, GDH11, Va116, VG, and GD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…The GST is grouped into different subclasses such as TAU, Phi, Lambda, Zeta, TCHQD, Theta, GHR, EF1B and DHAR based on the previous report [45]. Identification of GST genes in other plant species has been reported; for example, 55 GSTs in Arabidopsis [46], 38 GSTs from the apple (Malus domestica [38] and 82 GSTs in radish (Raphanus sativus) [47], 90 in potato (Solanum tuberosum L.) [48], 90 in tomato [49], 74 in soybean (Glycine max) [50], 85 in pepper (Capsicum annuum) [51], 92 in grapes (Vitis vinifera) [52], 57 in pear (Pyrus communis L.) [43] and 59 in tobacco (Nicotiana tabacum) [53]. In this study, 40 GSTs were found in the eggplant genome and subsequently characterized (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The GST is grouped into different subclasses such as TAU, Phi, Lambda, Zeta, TCHQD, Theta, GHR, EF1B and DHAR based on the previous report [45]. Identification of GST genes in other plant species has been reported; for example, 55 GSTs in Arabidopsis [46], 38 GSTs from the apple (Malus domestica [38] and 82 GSTs in radish (Raphanus sativus) [47], 90 in potato (Solanum tuberosum L.) [48], 90 in tomato [49], 74 in soybean (Glycine max) [50], 85 in pepper (Capsicum annuum) [51], 92 in grapes (Vitis vinifera) [52], 57 in pear (Pyrus communis L.) [43] and 59 in tobacco (Nicotiana tabacum) [53]. In this study, 40 GSTs were found in the eggplant genome and subsequently characterized (Table 1).…”
Section: Discussionmentioning
confidence: 99%